Adding Value to New Zealand Eels by Aquaculture - Hirt-Chabbert, Jorge Andrés (Auckland University of Technology, 2011)
Freshwater eels are one of the world's most valuable cultured fish species. Although almost all worldwide eel production is derived from eel farms, no cultured eels are produced in New Zealand. Currently, the entire eel business in this country consists of catching shortfin (Anguilla australis) and longfin (A. dieffenbachii) in the wild and selling them on the local or international markets. However, changes in market specifications, production technology and wild eel stock restrictions have motivated an evaluation of culturing eels as a commercial route to contribute to regional economic development in New Zealand. This thesis describes a series of feeding trials that aim to show how to add value to the native New Zealand shortfin eel by developing a market-oriented eel product through aquaculture, and to provide a better understanding of some eel culturing strategies that may help improve fish production and reduce the eel-farm operational work. All trials were undertaken indoors in recirculation aquaculture systems (RAS) and fish were fed commercial pelleted feed. Most of these experiments were developed on yellow shortfin eel at the Aquaculture Laboratory of the AUT University, but one experiment on feeding stimulants was done at the Unitat de Cultius Experimentals (IRTA, Centre de Sant Carles de la Ràpita, Spain) on glass eel and elvers of the European eel, because of the resources needed. The main outcomes of this thesis are: (1) The development of a New Zealand eel product aligned with international market specifications on the fat content. It was possible to grow a fatty shortfin-eel product with 20 to 22% total fat starting from wild yellow eels with an initial fat content below 7%. From a human dietary perspective, the fat quality of the eel product obtained by culturing was appreciably superior (higher proportion of omega-3 fatty acids) than the fat of eels caught in the wild. (2) The achievement of good values of mean growth rate (SGR= 1.1% day-1) and feed conversion ratio (FCR ≤ 1.1) for rearing yellow shortfin eels. These values compared favourably with other eel species of similar size range, which indicates a good potential for culturing. (3) The rejection of a hypothesis that size grading can improve the proportion of fast-growers and reduce the high variation in individual growth rate of yellow shortfin eels. It was not possible to improve the individual growth rate of small eels (slow-growers) by having no large eels (fast-growers) in the same tank. These findings suggest that the wide variability in the individual growth rate performance of the eels is not primordially a consequence of the social interaction (hierarchical position) among tank-mates. (4) The confirmation of a hypothesis that feeding stimulants can improve the proportion of fast-growers and reduce the high variation in individual growth rate of juvenile eels. The use of feeding stimulants showed a beneficial effect on the growth rate, size distribution homogeneity, feed intake and digestive function. Although this study was performed on the European eel, the results are encouraging enough to warrant research on the use of stimulants on shortfin eel as a culturing technique to obtain a rapid and uniform fish growth. The outcomes of this research in conjunction with previous studies on the culture of shortfin glass eels and elvers indicate that the shortfin eel has good potential to be a cultured species. However, there are yet numerous aspects, mainly from a business and legislative perspective, which must be addressed before a new eel culture industry can be a reality in New Zealand.
Keywords: New Zealand eels; Aquaculture; Adding value